Phase I Study to Assess Safety of Laser-Assisted Topical Administration of an Anti-TNF Biologic in Patients With Chronic Plaque-Type Psoriasis - Bauer, Martin; Lackner, Edith; Matzneller, Peter; Al Jalali, Valentin; Pajenda, Sahra; Ling, Vincent; Böhler, Christof; Braun, Werner; Braun, Reinhard; Boesch, Maximilian; Brunner, Patrick M.; Zeitlinger, Markus (Frontiers in Medicine, 2021)
Ablative fractional laser treatment facilitates epidermal drug delivery, which might be an interesting option to increase the topical efficacy of biological drugs in a variety of dermatological diseases. This work aims at investigating safety and tolerability of this new treatment approach in patients with plaque-type psoriasis. Eight patients with plaque-type psoriasis were enrolled in this study. All patients received (i) ablative fractional laser microporation (AFL) of a psoriatic lesion with an Er:YAG laser + etanercept (ETA; Enbrel® solution for injection) (AFL-ETA), (ii) ETA alone on another lesion, and, if feasible, (iii) AFL alone on an additional lesion. Overall, all treatment arms showed a favorable safety profile. AFL-ETA improved the lesion-specific TPSS score by 1.75 vs. baseline, whereas ETA or AFL alone showed a TPSS score improvement of 0.75 points, a difference that was not statistically significant and might be attributable to differences in baseline scores. Topical administration of ETA to psoriatic plaques via AFL-generated micropores was generally well-tolerated. No special precautions seem necessary in future studies. Clinical benefit will need assessment in sufficiently powered follow-up studies.